Efficiency Of Procurement Of Main Raw Materials For Pizza Makers With Economic Order Quantity (EOQ) Approach - Wibowo, Wahyu Andri (IJOSMAS, 2022)
Papa Ron's Pizza is a small and medium business engaged in the culinary field, there are 5 types of main raw materials needed by Papa Ron's Pizza in making pizza, namely twin chakra flour, mozzarella cheese, dough blend, dougo canola oil and pizza sauce. So far, the company manages its inventory based on physical observations. Therefore, Papa Ron's Pizza procures raw material inventory so that its sales activities are not disrupted due to a lack of merchandise inventory. However, if the supply of raw materials is too large, Papa Ron's Pizza will risk a loss, namely damaged, lost, shrinking goods and so on which results in decreased sales of Papa Ron's Pizza. The author applies the Economic Order Quantity (EOQ) method to Papa Ron's Pizza for the five raw materials, namely Twin Cakra flour, mozzarella cheese, dough blend, dougo canola oil and pizza sauce. Before using the EOQ the procurement cost was obtained at IDR 21,361,400, - and after using the EOQ calculation, it was obtained at IDR 4,881,613,68, it can be concluded that the application of the EOQ method can save the total procurement cost of IDR 16,480,626.33, so The efficiency of raw material procurement at Papa Ron's Pizza can be achieved. Papa Ron's Pizza Park Royale Branch should use Economic Order Quantity (EOQ) in the procurement of raw materials, because the required procurement costs are lower.